Smooth talking stranger [compact disc, unabridged] : a novel - Kleypas, Lisa (Brilliance Audio, 2009)
Ella Varner shows up at the office of Jack Travis, a rich, tough Houston businessman, with a baby in her arms, claiming he is the father. Apparently, her sister gave birth to the baby and left it with Ella to take care of. After doing some investigating, Ella found Jack and wants him to take a paternity test to see if the baby is his.